2016
DOI: 10.1002/rrq.155
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Compounding Awareness Predicts Reading Comprehension in Young Chinese Students: A Longitudinal Study From Grade 1 to Grade 2

Abstract: Using a longitudinal sample of young Chinese students (fall and spring in grades 1 and 2: times 1–4, respectively) and growth curve analysis, this study examined whether the initial status and growth rates of compounding awareness from time 1 to time 4 uniquely contribute to reading comprehension at time 4 and whether word‐reading efficiency at time 4 mediates the association between initial status and growth in compounding awareness and reading comprehension at time 4. The results indicated that initial statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 47 publications
11
66
0
Order By: Relevance
“…Consistent with previous studies (e.g.,Cheng et al, 2017;McBride-Chang et al, 2005), MA was found to predict reading at the first assessment. Consistent with previous studies (e.g.,Cheng et al, 2017;McBride-Chang et al, 2005), MA was found to predict reading at the first assessment.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Consistent with previous studies (e.g.,Cheng et al, 2017;McBride-Chang et al, 2005), MA was found to predict reading at the first assessment. Consistent with previous studies (e.g.,Cheng et al, 2017;McBride-Chang et al, 2005), MA was found to predict reading at the first assessment.…”
mentioning
confidence: 83%
“…cumulative trajectory. Consistent with previous studies (e.g.,Cheng et al, 2017;McBride-Chang et al, 2005), MA was found to predict reading at the first assessment. More interestingly, MA at K2 (Time 1) uniquely predicted the growth rate of reading ability between K2 and K3 (Times 1-4), a period during which formal literacy instruction takes place.…”
mentioning
confidence: 83%
See 3 more Smart Citations